No place to hide Edward Snowden, the NSA, and the U.S. surveillance state - Greenwald, Glenn (New York, NY Metropolitan Books/Henry Holt, 2014)
"Investigative reporter for The Guardian and bestselling author Glenn Greenwald, provides an in-depth look into the NSA scandal that has triggered a national debate over national security and information privacy. With further revelations from documents entrusted to Glenn Greenwald by Edward Snowden himself, this book explores the extraordinary cooperation between private industry and the NSA, and the far-reaching consequences of the government's surveillance program, both domestically and abroad" -- from publisher's Web site
Keywords: Snowden, Edward J. -- 1983-.; United States. -- National Security Agency/Central Security Service; Leaks (Disclosure of information) -- United States; Whistle blowing -- United States; Electronic surveillance -- United States; Electronic books